A qualitative study of the value of simulation-based training for nursing students in primary care - Lucy Bray; Doris Østergaard (BMC, 2024)
Abstract Background Clinical placement is an essential component of nursing education, providing students with the opportunity to apply theoretical knowledge to practice. However, challenges such as lack of supervision and passive involvement in tasks can hinder the learning experience. Supplementing clinical placement with simulation-based training (SBT) has been explored as a potential solution, though this approach has been underexplored within primary care. This study aimed to explore the educational value of a supplemental SBT course for nursing students during primary care placement, as well as the adaption of this approach to a primary care setting. Methods A qualitative descriptive study was conducted at a medical education and simulation academy in Denmark. Sixth-semester nursing students on placement in primary care were invited to participate. The intervention consisted of a three-day simulation course covering core nursing competencies and common clinical conditions encountered within primary care. Simulation adopted a standardised patient approach. Data was collected using focus group interviews, which was analysed using inductive thematic analysis. Results Thirty-one nursing students participated in the study. Seven themes emerged from the analysis, including perceptions, educational value, simulation adjustments to primary care, educators' competencies, learning needs within primary care, challenges of clinical placement and career guidance. Generally, participants perceived the intervention positively, appreciating its relevance to their clinical placement and its educational impact in this context. Participants also provided insights into the adaptation of SBT to a primary care setting, as well as nursing students' learning needs within this context. Conclusion The findings indicate that the intervention had a positive impact on participant competencies within this context and enhanced their clinical practice within primary care. Furthermore, the results inform educators on how to effectively employ primary care-related SBT. Overall, this study supports the need for an increased application of SBT within primary care. Trial registration Not relevant.